The Correlation of LibGuides to Print and Electronic Book Usage: A Method for Assessing LibGuide Usage. Issue 1 (2nd January 2021) - Hicks, Sarah; White, Kristy; Behary, Rob
Abstract: This research project explores whether a correlation exists between the use of one university library's subject-specific LibGuides and print and electronic book usage in associated subject areas. Statistical analysis was applied to LibGuides usage statistics, integrated library system (ILS) circulation data, and ebook usage data provided by library vendors. Significant positive correlations were found between LibGuides usage and book and electronic book usage at several levels: generally, by subject, and by University school. By exploring the correlations, the researchers show how statistical analysis can be used to demonstrate the value of subject-specific LibGuides using objective metrics. The study may serve as a model to future researchers who wish to explore the relationship of LibGuides to other areas of library collections, and potentially to other services offered by the library. The study may help inform library managers in allocating resources appropriately regarding the creation and maintenance of LibGuides.